Isotopically labeled ozone: A new approach to elucidate the formation of ozonation products. (15th April 2023) - Sierra-Olea, Millaray; Kölle, Simon; Bein, Emil; Reemtsma, Thorsten; Lechtenfeld, Oliver J.; Hübner, Uwe
Highlights: Two model compounds were ozonated with 18 O3 to generate 18 O-labeled products (OPs). The OP of venlafaxine, venlafaxine N-oxide, can be used as 18 O/ 16 O ratio indicator. The 18 O /16 O ratio reflects the formation pathway of direct O-transfer products. Six of the seven OPs from the reaction of sulfamethoxazole with 18 O3 were labeled. 18 O3 used in complex water matrices can identify OPs formed by O-transfer reactions. Abstract: As ozonation becomes a widespread treatment for removal of chemicals of emerging concern from wastewater treatment plant effluents, there are increasing concerns regarding the formation of ozonation products (OPs), and their possible impacts on the aquatic environment and eventually human health. In this study, a novel method was developed that utilizes heavy oxygen ( 18 O2 ) for the production of heavy ozone ([ 18 O1 ]O2, [ 18 O2 ]O1, [ 18 O3 ]) to actively label OPs from oxygen transfer reactions. To establish and validate this new approach, venlafaxine with a well-described oxygen transfer reaction (tertiary amine -> N- oxide) was chosen as a model compound. Observed 18 O/ 16 O ratios in the major OP venlafaxine N- oxide (NOV) correlated with expected 18 O purities based on tracer experiments. These results confirmed the successful labeling with heavy oxygen and furthermore demonstrate the potential to monitor NOV as an indicator of 18 O/ 16 O ratios during ozonation. As a next step, 18 O/ 16 O ratios were used to elucidate the formation mechanism of previously described OPs from sulfamethoxazole (SMX). Seven OPs were detected including the frequently described nitro-SMX, which was formed with a maximum yield of 3.2% (of initial SMX). With the successful labeling of six of the seven OPs from sulfamethoxazole, it was possible to confirm their previously proposed formation pathways, and to distinguish oxygen transfer from electron transfer reactions. 18 O/ 16 O ratios in OPs indicate that hydroxylation of the aromatic ring and formation of nitro-groups mostly follows oxygen transfer reactions, while electron transfer reactions initiate the formation of hydroxylamine and the abstraction of NH2 leading to catechol.